(3bjGS LhOI GdNOeGJ GdUMjI (B/s - (3RYjJQ, aGJMs ((3GdLRGFQ(B: s (3OGQ GdHGMK ddfTQ hGdGTgGQ(B, s, 2023)
(3GdeONd Edi GdLhOI, GdNOeI GdUMjI,GdLhOI aj GdeDSSI GdUMjI,CHYGOgG hbjGS hJbjje LhOI GdNOeI GdUMjI HGdGVGaI Edi GdQbGHI(B.s
(3eQGLY U(B.119 (3U(B.s
Keywords: (3GdQbGHI GdUMjIs